Adolescent player development within institutional constraints in academy football - Hill, M.; Mitchell, S.; Brookman, J.; McGee, D.; Cumming, S. P. (International Journal of Sports Science & Coaching, 2025)
This study aimed to investigate academy football coaches` perceptions and experiences of managing adolescent growth and maturation within the constraints of an English Premier League academy. Using a longitudinal mixed method design, 98 under 12-16 players were assessed for maturity status, growth velocities and match performance grade. Interviews were conducted in parallel, with their nine respective coaches. The quantitative and qualitative data were then combined to generate a rich, contextualised understanding. One case study is also presented as an archetypal example. Findings are presented in three themes. Coaches described the conflict between the value of winning and player development, difficulties in judging potential and performance, and the challenges of developing players in an elite competitive environment. Findings emphasise the intricacies of managing and developing adolescent athletes in academy football. Coaches in this study were challenged by the individual differences in growth and maturation and the elite, competitive and selective nature of football academies and the constraints of this environment exacerbate these challenges.